High-volume training and the effects of altered protein intake on nitrogen balance
Swimmers were studied covering an average of 18,000 m per day. When caloric requirements were not met, the body used protein as a fuel instead of using it to repair and build muscle tissue. Implications: In heavy training, carbohydrate supplementation as well as a high carbohydrate diet have to be rigidly followed. In addition, daily protein intake has to be increased to nearly 2 grams for every kg of body weight. These two actions are done to ensure that anabolic metabolism remains dominant and a positive nitrogen balance is maintained. These requirements will necessitate different feeding and eating habits for serious swimmers. Teaching and developing adherence to them will be difficult at first but should be easier when performances improve. It may be helpful to compare the performances of a month of "normal" (insufficient) diet and a month of supplemented diet. If an obvious benefit is shown then adherence will not be a problem. A more obvious index of insufficient carbohydrate and protein in the diet is weight loss during important training phases. When that loss is coupled with poor performance one is usually safe in attributing the problem to insufficient energy supplied in the diet.